Disfagia pada Lansia Rapuh - Vina Megitasari; Rachmat Zulkarnain Goesasi; Irma Ruslina Defi (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
Effective and safe swallowing is one of the basic needs for human survival. Dysphagia or swallowing disorders often occur in the elderly and increase with age. Patients often do not complain of dysphagia and compensate by modifying the texture of the food. Frailty is associated with an increased prevalence of dysphagia. Difficulty of chewing, formation and positioning bolus are associated with dysphagia. In addition, dysphagia can cause weakness because there is a disturbance due to decrease nutritional status, muscle function, and can cause recurrent aspiration pneumonia. Frailty and dysphagia can be described as a cycle and affect each other. Several interventions were carried out to overcome dysphagia, either compensatory, rehabilitative, or a combination of both.